2024
DOI: 10.1039/d4ob00044g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of difluoromethylated spiropyrazolones via [3 + 2] cycloaddition of difluoroacetohydrazonoyl bromides with alkylidene pyrazolones

Yang Feng,
Yuanyuan Ren,
Duoduo Tang
et al.

Abstract: An effective [3+2] cycloaddition reaction of difluoromethyl or trifluoromethyl hydrazonoyl bromides with alkylidene pyrazolones was disclosed. The method provides an efficient approach to access a variety of highly functionalized fluoroalkyl...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Following the DFT calculation and the experimental results as well as the literature reports, we tentatively proposed a possible mechanism by using the reaction between acetohydrazonoyl bromide 2a and α-phenylvinylsulfonium salt 1a (Scheme ). At first, elimination of HBr from 2a in the presence of K 2 CO 3 afforded nitroimine A and its resonance form B , which performed a synergistic [3 + 2] cycloaddition reaction with α-phenylvinylsulfonium salt 1a to produce pyrazoline intermediate D .…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Following the DFT calculation and the experimental results as well as the literature reports, we tentatively proposed a possible mechanism by using the reaction between acetohydrazonoyl bromide 2a and α-phenylvinylsulfonium salt 1a (Scheme ). At first, elimination of HBr from 2a in the presence of K 2 CO 3 afforded nitroimine A and its resonance form B , which performed a synergistic [3 + 2] cycloaddition reaction with α-phenylvinylsulfonium salt 1a to produce pyrazoline intermediate D .…”
Section: Resultsmentioning
confidence: 83%
“…Nitrile imines, generated in situ from hydrazonyl halides in the presence of a base, are very reactive and important 1,3-dipoles used for the construction of pyrazoles, pyrazolines, and other bioactive heterocycles through 1,3-dipolar cycloaddition reactions. , However, the [3 + 2] cycloaddition reactions of vinylsulfonium salts with nitrile imines have remained unknown until now, although the [3 + 2] annulation reaction of vinylsulfonium salts with diazo compounds was reported in 2023 (Scheme e) . In our previous research works on the development of new strategies for the synthesis of fluorinated heterocycles, it was found that difluoroacetohydrazonoyl bromides, which could generate in situ difluoromethyl nitrile imines in the presence of base, are reactive and efficient difluoromethyl building blocks for the synthesis of difluoromethyl heterocyclic compounds . As our ongoing research works, we would like to report herein the [3 + 2] cycloaddition of acetohydrazonoyl halides and vinylsulfonium salts to provide pyrazole derivatives in good yields (Scheme ).…”
Section: Introductionmentioning
confidence: 99%